Improvement of the sensitivity of EPR spin trapping in biological systems by cyclodextrins: A model study with thylakoids and photosystem II particles - Šnyrychová, Iva (Free radical biology & medicine, 2010)
Electron paramagnetic resonance (EPR) spin trapping spectroscopy is an important method used in free radical research; however, its application in biological systems is hindered by EPR silencing of spin adducts. Previous studies in superoxide-generating chemical systems have shown that spin adducts can be partially stabilized by cyclodextrins. In this work, for the first time, this proposed protective effect of cyclodextrins is investigated in a real biological sample-in isolated thylakoid membranes and photosystem II (PSII) particles with EMPO as a spin trap. It is shown that (i) randomly methylated beta-cyclodextrin and 2-hydroxypropyl-beta-cyclodextrin form inclusion complexes with EMPO-superoxide adducts (EMPO-OOH), (ii) both cyclodextrins increase the intensity of the EMPO-OOH EPR signal in PSII particles up to five times, (iii) higher EMPO-OOH EPR signal intensity is a result of increased stability of EMPO-OOH, and (iv) the extent of the protection of EMPO-OOH adduct provided by cyclodextrins is different in thylakoids and PSII particles. Along with the spin trapping data, the toxicity of cyclodextrins is also discussed with particular focus on photosynthetic preparations. The presented data show that both tested cyclodextrins can be used as valuable tools to improve the sensitivity of spin trapping in biological samples.
Keywords: Pyrroles; Superoxides; superoxidy; beta-Cyclodextrins; Cyclodextrins; techniky in vitro; Electron Spin Resonance Spectroscopy; Spinacia oleracea; pyrroly; spin trapping; elektronová paramagnetická rezonance; Thylakoids; cyklodextriny; tylakoidy; In Vitro Techniques; Sensitivity and Specificity; senzitivita a specificita; Photosystem II Protein Complex; beta-cyklodextriny; Spin Trapping; fotosystém II (proteinový komplex)